THE IMPLEMENTATION OF RISK MANAGEMENT AND ITS EFFECT ON GOOD COOPERATIVE GOVERNANCE AND SUCCESS - Sugiyanto Sugiyanto; Anggi Andriani Rahayu (Faculty of Economics and Business, Universitas Gadjah Mada, 2018)
The Cooperative success must be support by Good Cooperative Governance and implementation of risk management. This study identifies risk management, especially in savings and loan cooperatives, and to test and prove empirically the effects of the implementation of risk management on good cooperative governance and the cooperative success. The research method used a descriptive quantitative analysis and saturation sampling techniques; while the size of the population was 73 persons, consisting of various cooperatives’ boards of directors, supervisors, managers, and administrators. The primary data needed in this study were obtained by using a survey method which involved questionnaires and conducting structured interviews. This study uses a statistical approach by using path analysis. The result of this study shows that two categories of risks can be identified, which are minor and insignificant risks. A minor risk includes the credit risk and strategic risk, and an insignificant risk includes six risks: market risk, liquidity risk, operational risk, legal risk, reputation risk and compliance risk. Based on the statistical analysis, the indication is that there is no effect from the implementation of risk management on a cooperative’s success, but there is an effect from the implementation of risk management on good cooperative governance, and good cooperative governance has an effect on a cooperative’s success. Indirectly, a cooperative’s success is not influenced by the implementation of risk management, but it is influenced by the implementation of risk management through good cooperative governance as an intervening variable.